2002
DOI: 10.1111/j.1095-8312.2002.tb02080.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and evolution in the genus Apodemus (Muridae: Rodentia)

Abstract: Genetic variation was studied using protein electrophoresis of 28-38 gene loci in 1347 specimens of Apodemus agrarius, A. peninsulae, A. flavicollis, A. sylvaticus, A. alpicola, A. uralensis, A. cf. hyrcanicus, A. hermonensis, A. m. mystacinus and A. m. epimelas The data also suggest a recent separation of members of the latter group from a common ancestor, and subsequent rapid radiation, making it difficult to infer phylogenetic relationships. Some taxonomic implications of the results are discussed further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…2002). Both morphological and molecular data have shown that A. mystacinus , as presently defined, consists of two separate species, one present in the western ( Apodemus epimelas ) and the other in the eastern parts of the range (Storch 1977; Filippucci et al. 2002; Michaux et al.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…2002). Both morphological and molecular data have shown that A. mystacinus , as presently defined, consists of two separate species, one present in the western ( Apodemus epimelas ) and the other in the eastern parts of the range (Storch 1977; Filippucci et al. 2002; Michaux et al.…”
Section: Introductionmentioning
confidence: 91%
“…For the present study, 20 individuals belonging to the genus Apodemus were analyzed. The samples were previously identified by morphological and allozyme analysis (Filippucci et al. 2002; Michaux et al.…”
Section: Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Populations of the rocky mouse, Apodemus mystacinus, have similar karyotypes both in the Balkans and Asia Minor; extraordinarily deep genetic divergence was found between them, however (Filippucci et al, 2002). Another species distributed both in the Balkans and Asia Minor is the Guenther's vole, Microtus guentheri.…”
Section: Zimamentioning
confidence: 99%
“…Ap par ent mor pho log i cal sim i lar ity with con tin u ous pat tern of vari a tion from one spe cies to the other was ini tially in ter preted as the re sult of hy brid iza tion and introgression (eg Witte 1964, Amtmann 1965, Bauer et al 1967. How ever, at the same time this po si tion was doubted on the ba sis of mor pho log i cal ev i dence (Niethammer 1969) and later re jected by nu merous mo lec u lar stud ies (for sum mary, see Filippucci et al 2002).…”
mentioning
confidence: 99%